2021
DOI: 10.1002/eap.2268
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing declines of woodland birds: Are restoration plantings making a difference?

Abstract: Woodland birds are a species assemblage of conservation concern, and their persistence in fragmented agricultural landscapes is dependent on both the preservation of existing woodland remnants and the implementation of restoration plantings. However, little is known about the habitat-use and persistence of birds in fragmented agricultural landscapes. We present a detailed, population-oriented study of woodland birds in temperate eucalypt woodland restoration plantings and remnant woodland patches in the Southw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…We attempted to account for variation in songbird life histories by establishing control areas where possible, and by including in a second songbird response metric only species we considered to be small‐bodied residents. Data from control areas showed that some spatio‐temporal variation in songbird occupancy patterns—even within species we considered resident—is likely to be independent of any effects of noisy miner management (Belder et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We attempted to account for variation in songbird life histories by establishing control areas where possible, and by including in a second songbird response metric only species we considered to be small‐bodied residents. Data from control areas showed that some spatio‐temporal variation in songbird occupancy patterns—even within species we considered resident—is likely to be independent of any effects of noisy miner management (Belder et al, 2021).…”
Section: Discussionmentioning
confidence: 99%